KUALITAS MINUMAN SARI BIJI NANGKA (Artocarpus heterophyllus)DENGAN PENAMBAHAN JAHE MERAH(Zingiber officinale varrubrum rhizoma) - Syahri Fadhila Al-Farid; Jamaluddin Jamaluddin; Andi Sukainah (Universitas Negeri Makassar, 2022)
This study aims to determine the quality of jackfruit seed juice drinks with the addition of red ginger and to determine the level of acceptance of panelists on jackfruit seed juice drinks. Parameters observed included water content, protein content, carbohydrate content and organoleptic including color, taste, aroma and texture. This study used a Completely Randomized Design (CRD) consisting of one factor, namely the concentration of red ginger juice with four treatments, namely: 0%, 6%, 12%, 18%, each repeated three times. The results showed that jackfruit seed juice drink with the addition of 18% red ginger was the best treatment from the results of organoleptic tests. The proximate test results showed that the best treatment was 3.13% water content in 12% ginger treatment, 2.17% protein in 18% red ginger treatment and 95.61 carbohydrate in 18% red ginger treatment.